Pengaruh Penggunaan Model Pembelajaran Contextual Teaching and Learning pada Pembelajaran PKn Siswa Kelas V SD Negeri 2 Gelumbang - Oktarianti, Risti; Hermansah, Bambang; Marleni, Marleni (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to determine the effect of using the Contextual Teaching and Learning learningmodel on Civics Learning for fifth grade students of SD Negeri 2 Gelumbang. The application ofthe learning model is to make it easier for teachers to convey the material being studied tostudents so that students can understand the material being taught. This study uses anExperimental research method with quantitative data types that use data collection by conductingObservations, Tests and Documentation involving 2 classes as Experiment class and Control classwith a sample of 48 students with good categories, VA class is used as Experiment class and VB is used as class The number of control students in the Experiment class is 25 students while in the Control class 23 students. Based on the results of the study, in the Experimental class there was an increase in learning outcomes with an average value of 80 so there was an influence on the use of the Contextual Teaching and Learning learning model in PKN learning for fifth grade students, thus teachers could apply the Contextual Teaching and Learning learning model to student learning in class. The calculation of this study uses the SPSS 22 application. So there is asignificant influence on the use of the Contextual Teaching and Learning Learning Model in PKNlearning for the fifth grade students of SD Negeri 2 Gelumbang.